PENGABDIAN MASYARAKAT KADERISASI RUKUN KEMATIAN DESA MANGUNREJO KECAMATAN KALIKAJAR (Journal Edutama Multidisciplinary Indonesian, 2024)
The Death Pillar is a social activity forum owned by residents, which provides services to members in the form of death services, such as: corpse care (bathing, shrouding and performing funeral prayers) to delivering the body to the cemetery. However, what happened in the community in Mangunrejo Kalikajar Village found that there was no death pillar or schedule for reviewing the body so that when this happened, all residents had to wait for the cleric to take care of it while he was traveling far away. So the MBKM bR KPM Community Service activity from the 49th KPM group from UNSIQ Wonosobo provided education with Mr. Fauzi as a resource person from the KUA Kec. Kalikajar who would provide direction and procedures according to Islamic law and Fiqh on how to organize the body from the beginning to burial.